2018
DOI: 10.1093/ofid/ofy194
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Parenteral Antimicrobial Therapy Among People Who Inject Drugs: A Review of the Literature

Abstract: Hospitalizations for people who inject drugs (PWID) with infectious complications requiring prolonged antibiotic therapy are increasing in the context of the opioid epidemic. Although outpatient parenteral antimicrobial therapy (OPAT) is routinely offered to patients without a history of injection drug use (IDU), PWID are often excluded from consideration of OPAT. To better assess the evidence base for the safety and effectiveness of OPAT for PWID, we conducted a review of the published literature. Results sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 40 publications
1
79
1
Order By: Relevance
“…Many transplant centers consider OUDs, chronic opioid use, or opioid agonist treatment to be a relative contraindication to proceeding with transplantation [113][114][115]. Similarly, people with a history of injection drug use, or people on opioid agonist treatment (irrespective of injection drug use history), are routinely excluded from receiving post-acute care in skilled nursing facilities [116] or parenteral antimicrobial therapy in outpatient settings [117,118]. Physicians identified as having OUDs who are required to enroll in physician health programs are often required to adhere to abstinence-only approaches and discontinue opioid agonist treatment as a condition of maintaining professional licensure [119].…”
Section: Structural Stigmamentioning
confidence: 99%
“…Many transplant centers consider OUDs, chronic opioid use, or opioid agonist treatment to be a relative contraindication to proceeding with transplantation [113][114][115]. Similarly, people with a history of injection drug use, or people on opioid agonist treatment (irrespective of injection drug use history), are routinely excluded from receiving post-acute care in skilled nursing facilities [116] or parenteral antimicrobial therapy in outpatient settings [117,118]. Physicians identified as having OUDs who are required to enroll in physician health programs are often required to adhere to abstinence-only approaches and discontinue opioid agonist treatment as a condition of maintaining professional licensure [119].…”
Section: Structural Stigmamentioning
confidence: 99%
“…However, the studies tended to have small sample sizes and did not evaluate new BSIs as a complication. A literature review of 10 studies on OPAT in PWID 34 found high treatment completion, low mortality, and few catheter-related complications, comparable to rates in non-PWID populations. Another study 35 implemented a 9-point tool to identify PWID candidates for OPAT, with low-risk PWID discharged to complete treatment as outpatients.…”
Section: Discussionmentioning
confidence: 90%
“…Due to reluctance of IVDA for prolonged hospital admission and the concerns related to their discharge on intravenous antibiotic therapy, a few studies have studied the possibility of treating IE in these patients with short course antibiotic therapy [23].…”
Section: Managementmentioning
confidence: 99%